2020
DOI: 10.1590/2178-2547-bgoeldi-2019-0084
|View full text |Cite
|
Sign up to set email alerts
|

O Sambaqui do Recreio: geoarqueologia, ictioarqueologia e etnoarqueologia

Abstract: Resumo O presente artigo apresenta o processo de ocupação sambaquieiro na barreira da Itapeva, contextualizando os sítios e os seus construtores na cronologia, bem como as escolhas para inserção em uma paisagem marcada pela dinâmica das transformações paleoambientais. A implantação do Sambaqui do Recreio sobre uma planície costeira em formação demonstra uma escolha cultural calcada em um modo de vida milenar que já se desenvolvia na costa sul/sudeste brasileira há quase dois mil anos. Se, por um lado, as escav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…In the analyzed sambaquis' records, five individuals were small cetaceans (Delphinidae and the common bottlenose dolphins, Tursiops truncatus) and all individuals of Eubalaena australis were young. As sambaqui builders lived mainly in environments close to the sea and had advanced technology and strategy for fishing, possessing braided fibre nets, weights, stakes, hooks, harpoons/spears, and boats (Calippo 2011, Barbosa-Guimarães 2013, Ferreira et al 2018, 2019, Wagner et al 2020, Fossile et al 2023a, they had the necessary toolkit to actively hunt smaller-sized cetaceans, in the same way that they also exploited a diversity of sharks and rays, exemplifying hunt/fisheries of large/ medium specimens/individuals (Lopes et al 2016, Fossile et al 2020. However, these animals may also have been bycatch, which is more significant on small cetaceans such as dolphins and whale juveniles or calves, which are more likely to become entangled in nets than larger animals (Knowlton et al 2012, Brownell Jr. et al 2019.…”
Section: Discussionmentioning
confidence: 99%
“…In the analyzed sambaquis' records, five individuals were small cetaceans (Delphinidae and the common bottlenose dolphins, Tursiops truncatus) and all individuals of Eubalaena australis were young. As sambaqui builders lived mainly in environments close to the sea and had advanced technology and strategy for fishing, possessing braided fibre nets, weights, stakes, hooks, harpoons/spears, and boats (Calippo 2011, Barbosa-Guimarães 2013, Ferreira et al 2018, 2019, Wagner et al 2020, Fossile et al 2023a, they had the necessary toolkit to actively hunt smaller-sized cetaceans, in the same way that they also exploited a diversity of sharks and rays, exemplifying hunt/fisheries of large/ medium specimens/individuals (Lopes et al 2016, Fossile et al 2020. However, these animals may also have been bycatch, which is more significant on small cetaceans such as dolphins and whale juveniles or calves, which are more likely to become entangled in nets than larger animals (Knowlton et al 2012, Brownell Jr. et al 2019.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of shell mounds in other Brazilian coastal areas (e.g. São Paulo – Cosipa I, II, IV – Figuti, 1993; Santa Catarina – Wagner et al, 2020; Lagoa dos Freitas – Santos et al, 2018; Jabuticabeira II – Klokler et al, 2010; and Rio Grande do Sul – Milheira et al, 2019) demonstrated that the whitemouth croaker has been an important target of fishing activity since at least 5000 cal BC. This species has also been documented in coastal shell mounds outside Brazil, in Uruguay (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…1 A pesca como elemento de coesão social foi já abordada em Diegues (2004) para as comunidades tradicionais do Brasil Meridional e Wagner; Silva (2014Silva ( , 2022 têm consolidado o uso destas categorias analíticas para o estudo das sociedades indígenas costeiras do Sul do Brasil. Especialmente no que tange à arqueologia dos sambaquis Hilbert, 2020;Gaspar, 2022;Pompeu;Silva, 2023) Silva (2021aSilva ( , 2021b.…”
Section: Notasunclassified